2002
DOI: 10.1097/00043764-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile of Firefighters Over Time: Opportunities for Prevention

Abstract: Heart disease is the primary cause of on-duty deaths in firefighters, but little is known about their lipid profile. We evaluated the lipid profile in relation to other cardiovascular disease risk factors in 321 firefighters at a baseline examination. Prospective comparisons were performed for 285 firefighters, who were enrolled in a statewide medical surveillance program, and had complete follow-up data for 4 years. The average cholesterol level in firefighters declined from 224 mg/dL at baseline (1996-1997) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
4
18
3
Order By: Relevance
“…We previously reported a 33% prevalence of obesity among the professionally active control firefighters, 14 which increased to 40% 4 years later. 15 Similar cross-sectional results were also observed in a Texas cohort. 22 Additionally, Womack et al 23 found that both exercise tolerance and lean body mass were below agepredicted averages in another firefighter cohort.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We previously reported a 33% prevalence of obesity among the professionally active control firefighters, 14 which increased to 40% 4 years later. 15 Similar cross-sectional results were also observed in a Texas cohort. 22 Additionally, Womack et al 23 found that both exercise tolerance and lean body mass were below agepredicted averages in another firefighter cohort.…”
Section: Discussionsupporting
confidence: 66%
“…We have previously shown that hypertension and dyslipidemia are often inadequately treated among professionally active Massachusetts firefighters and that uncontrolled hypertension is associated with a higher risk of adverse changes in employment status. [15][16][17] Therefore, we believe that risk factor screening alone is insufficient, and fire department medical programs should include incentives to promote more aggressive risk factor reduction. These should include measures for progressively controlling hypertension, 17,26 which is a treatable illness yet one whose failure to control accounted for almost 10% of heart retirements and most likely contributed to others.…”
Section: Discussionmentioning
confidence: 99%
“…8 Firefighters perform strenuous activities under stressful conditions and at the same time may have unfavorable CVD risk factor profiles. 9,10 It is well known that obesity is an established risk factor for cardiovascular disease and that it is associated with a clustering of other CVD risk factors, our group having previously reported on the relatively high prevalence of obesity among firefighters. 11,12 In addition, the medical literature strongly supports that left ventricular hypertrophy (LVH) is associated with a higher risk of cardiovascular morbidity and mortality.…”
mentioning
confidence: 92%
“…1 Several studies have documented increased cardiovascular risk factors in firefighters, including high levels of obesity. [10][11][12][13][14][15] Cardiovascular risk factors have unfavorable impact on arterial function, including decreased endothelial function, 16 and increased arterial stiffness, 17 and central blood pressure (BP), 18 all of which are predictive of allcause cardiovascular mortality. 13,19 Furthermore, higher aortic stiffness is associated with increased risk for a cardiovascular event.…”
Section: Introductionmentioning
confidence: 99%